Mechanochemically designed bismuth-based halide perovskites for efficient photocatalytic oxidation of vanillyl alcohol. Issue 20 (6th May 2022) - Estrada-Pomares, José; Ramos-Terrón, Susana; Lasarte-Aragonés, Guillermo; Lucena, Rafael; Cárdenas, Soledad; Rodríguez-Padrón, Daily; Luque, Rafael; de Miguel, Gustavo
Abstract : Mechanochemically synthesized bismuth-based halide perovskites are reported as efficient and stable photocatalytic nanomaterials for vanillyl alcohol oxidation to vanillin. Abstract : Halide perovskite materials (HPMs) have been recently employed as photocatalysts in H2 generation, CO2 reduction and organic synthesis. However, the high toxicity of lead is directing research towards Pb-free halide perovskites with bismuth as the main candidate to replace Pb. This contribution discloses the synthesis of two bismuth-based halide perovskites with chemical compositions Cs2 AgBiBr6 and Cs3 Bi2 Br9 via a solvent-free mechanochemical process in a ball mill. The obtained perovskite powders were characterized via X-ray diffraction, scanning electron microscopy (SEM) and absorption and photoluminescence (PL) steady-state and time-resolved spectroscopy. Cs2 AgBiBr6 was able to absorb more in the visible region ( E g = 2.12 eV) as compared to Cs3 Bi2 Br9 ( E g = 2.53 eV). Additionally, PL time decays were considerably longer for Cs2 AgBiBr6 ( τ av = 740 ns) with respect to Cs3 Bi2 Br9 ( τ av = 0.3 ns). Both photo-systems were employed in the oxidation of vanillyl alcohol to vanillin, an aldehyde derivative, under UV or visible illumination. Moderate values of photocatalytic conversion (15–30%) were observed except for Cs2 AgBiBr6 under visible light irradiation, where 95% conversion could be obtained after only 80 minutes of exposition. PL measurements with the fluorescent probe hydroethidine and electron spin resonance (ESR) demonstrated the formation of superoxide radical species (˙O2 − ) after photoexcitation, with a larger concentration observed for Cs2 AgBiBr6 under visible light due to higher absorption and longer lifetime of the photogenerated charge carriers. Time-resolved PL measurements of both catalysts mixed with vanillyl alcohol powder shed light on the oxidation step upon irradiation taking place due to a hole transfer process from the valence band of the catalysts.